Pathogenesis of Influenza A(H7N9) Virus in Aged Nonhuman Primates. (20th May 2020) - Fukuyama, Satoshi; Iwatsuki-Horimoto, Kiyoko; Kiso, Maki; Nakajima, Noriko; Gregg, Robert W; Katsura, Hiroaki; Tomita, Yuriko; Maemura, Tadashi; da Silva Lopes, Tiago Jose; Watanabe, Tokiko; Shoemaker, Jason E; Hasegawa, Hideki; et al.
Abstract: The avian influenza A(H7N9) virus has caused high mortality rates in humans, especially in the elderly; however, little is known about the mechanistic basis for this. In the current study, we used nonhuman primates to evaluate the effect of aging on the pathogenicity of A(H7N9) virus. We observed that A(H7N9) virus infection of aged animals (defined as age 20–26 years) caused more severe symptoms than infection of young animals (defined as age 2–3 years). In aged animals, lung inflammation was weak and virus infection was sustained. Although cytokine and chemokine expression in the lungs of most aged animals was lower than that in the lungs of young animals, 1 aged animal showed severe symptoms and dysregulated proinflammatory cytokine and chemokine production. These results suggest that attenuated or dysregulated immune responses in aged animals are responsible for the severe symptoms observed among elderly patients infected with A(H7N9) virus. Abstract : Aged cynomolgus macaques experienced greater symptom severity than younger animals after A(H7N9) virus infection because of immune senescence or dysregulated immune responses.